간호학생들의 문제중심학습이 학습자기효능감, 문제해결능력, 비판적 사고성향, 의사소통능력, 공감에 미치는 영향 - 이정; 김혜진; 김소연 (다문화건강학회지, 2024)
Purpose: This study aimed to develop and evaluate the effects of a nursing process education program using a prob- lem-based learning approach for undergraduate nursing students. Methods: The study employed a single-group pre-post design. A total of 35 nursing students were recruited from the batch of sophomore nursing students. Learning self-efficacy, problem-solving ability, critical thinking tendency, communication ability, and empathy were analyzed. Results: There were statistically significant differences in the problem-solving ability (t=-2.07, p<.05), critical thinking ten- dency (t=-2.17, p<.05), and communication ability (t=-2.53, p<.05). Conclusion: It is suggested that educational programs for nursing students be developed by applying various teaching and learning methods based on these results. KCI Citation Count: 0